Palaeohydrological modelling of Ace Lake, Vestfold Hills, Antarctica - Roberts, D; Jason Roberts; Gibson, JAE; Andrew McMinn; Heijnis, H (1999)
The major influences on the salinity and water level of an Antarctic lake are parameterized and a palaeohydrological model linking the palaeosalinity of an Antarctic lake to the palaeohydrology of the lake is developed. Climatic change in this lake is recorded in the evaporative loss trend reconstructed from water level and lakewater salinity estimates. A decrease in salinity between ~700 and 200 years BP corresponds with c. 5 m increase in water level over the same time period. Both water level and lakewater salinity then stabilize in the last ~200 years BP. The palaeohydrological model derived from the changes inferred in salinity and water level shows that there is no significant change in evaporation for the last ~700 years but that a lower evaporation period is evident at ~150-200 years BP suggestive of a mild 'Little Ice Age' event in the Vestfold Hills.